Quantifying charge carrier density in organic solar cells by differential charging techniques - Kyohei Nakano; Yujiao Chen; Keisuke Tajima (AIP Advances, 2019)
Accurate determination of charge carrier density in organic solar cells under light irradiation is essential because charge carrier density is directly related to the bimolecular recombination rate and open-circuit voltage of the cells. We investigate the robustness of transient photovoltage/current (TPV/C) and impedance spectroscopy (IS) to interference from the geometric capacitance of the cells (Cgeo) during quantification of the charge carrier density. TPV/C and IS accurately quantify the charge carrier density of bulk heterojunction cells with small Cgeo. For planar heterojunction cells with a larger Cgeo contribution, IS fails to separate the charge carriers in the organic layer from those in the electrodes. In contrast, TPV/C eliminates the effect of Cgeo and gives a reasonable estimation of the charge carrier density in the organic layer with the planar heterojunction, demonstrating that TPV/C is more robust than IS to interference from Cgeo of the cells.